Public investment and economic activity in Mexico, 1925-1981 - Felipe de Jesús Fonseca; Manuel Gómez-Zaldívar; Daniel Ventosa-Santaulària (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
The authors construct a historical database of public investment (both total and broken down into its main components) for the period 1925 to 1981 in order to measure its impact on economic activity. Given the possible presence of crowding-out effects between public investment and private investment, in their analysis they control for the latter. The results suggest that: i) public investment had a significant impact on output, one which varies depending on the category of public investment considered, and; ii) private and public investment are positively related, i.e., public investment has a crowding-in effect on private investment, and both have a positive and significant impact on GDP. The results contrast with those of previous studies that have analyzed this relationship, though using a different time period, one that includes the economic liberalization era. Nevertheless, these differences can be rationalized by the findings of Ilzetzki et al. (How Big (Small?) are Fiscal Multipliers? 2013), who point out that key country-specific characteristics such as trade openness and the exchange rate regime are determinant in the relationship between public investment and output.
http://dx.doi.org/10.7910/DVN/JYCLAN
Keywords: N16; H54; C32; 330; economic activity; federal public investment; long-term equilibrium relationship